No aspect of structure should be left behind in relation to student autonomous motivation - Mouratidis, Athanasios; Michou, Aikaterini; Telli, Sibel; Maulana, Ridwan; Helms-Lorenz, Michelle (British Journal of Educational Psychology, 2022)
Background Provision of structure in classroom settings constitutes one of the pillars of conducive learning environments. However, little is known whether the particular elements of provided structure—namely, contingency, clear expectations, help and support, and monitoring—are equally important for student learning and motivation. Aims In this cross-sectional study, we aimed to investigate to what extent students’ autonomous motivation is linearly and curvilinearly related to their perceptions of their teachers’ contingency, clear expectations, help and support, and monitoring. Sample Participants were 12,036 Turkish adolescent students (age range: 15–19 years; 54.4% males) from 446 classes, nested into 24 public schools. Methods Cross-sectional, based on student ratings of their self-determined motivation and their teacher structure provision and autonomy support. Results Multilevel and ordinary least-squares polynomial regression analyses showed all the four perceived structure elements to predict autonomous motivation, with expectations and contingency (especially when coupled with monitoring) being even more important predictors than the other elements. Response surface analyses also showed strong positive relation between autonomous motivation and all the possible pairs of the four elements of perceived structure along the line of congruence, suggesting an additive effect when teachers are thought to be contingent and helpful and supportive (or monitor their students, or clearly communicate their expectations). Conclusions These findings imply the key role that teachers could play in enhancing their students’ autonomous motivation by providing all the elements of structure.